ORIGIN and EVOLUTION of DOMESTIC CATTLE - Ajmone-Marsan, Paolo; Garcia, José Fernando [UNESP] (Universidade Federal do Rio Grande do Sul (UFRGS), 2008)
The origin and evolution of domestic cattle have recently moved to the forefront of the scientific literature in consideration of their links to human history and to decisions on Genetic Resources conservation strategies. DNA from modern and ancient Bos samples is being analysed to reconstruct, in cooperation with archaezoology, the main events and forces that shaped nowadays cattle genetic diversity. Still, a number of open questions remain, that hopefully will be answered with the help of new technologies and the combined analysis of worldwide data.
Keywords: Molecular markers; mtDNA; biodiversity; phylogeography; Bos indicus; Bos taurus